How does a physician's accurate understanding of a cancer patient's unmet needs contribute to patient perception of physician empathy?. Issue 6 (June 2015) - Lelorain, Sophie; Brédart, Anne; Dolbeault, Sylvie; Cano, Alejandra; Bonnaud-Antignac, Angélique; Cousson-Gélie, Florence; Sultan, Serge
Highlights Unmet supportive care needs decrease patient perception of physician empathy (PE). Physician accurate understanding buffers the adverse effect of these unmet needs on PE. The buffering effect occurs when patients are highly expressive. The buffering effect occurs when physician perceived poor rapport with the patient. In certain conditions, accurate understanding protects the doctor-patient relationship.